2013
DOI: 10.1097/sga.0b013e318280f867
|View full text |Cite
|
Sign up to set email alerts
|

Open or Laparoscopic Surgery for Colorectal Cancer

Abstract: Laparoscopic surgery for colorectal cancer has been used with success since 1991. During the last decade, many studies have compared laparoscopic surgery with open colectomy. The aim of this retrospective study was to present the advantages and disadvantages of laparoscopic and open colectomy for cancer, focusing on the postoperative care of patients. Eighty-eight consecutive patients suffering from cancer of the colon and rectum, surgically treated, were studied. They were divided into 2 groups: Group A patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Laparoscopic colorectal surgery caused higher surgery expenditure (P=0.003) and total hospitalization costs (P<0.001) compared with open surgery. Kapritsou et al (28) found that the surgery costs in the laparoscopic group were significantly higher than those in the open surgery group. In addition, Steele et al (29) reported that the total hospitalization costs in the laparoscopic group were significantly higher than those in the open surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic colorectal surgery caused higher surgery expenditure (P=0.003) and total hospitalization costs (P<0.001) compared with open surgery. Kapritsou et al (28) found that the surgery costs in the laparoscopic group were significantly higher than those in the open surgery group. In addition, Steele et al (29) reported that the total hospitalization costs in the laparoscopic group were significantly higher than those in the open surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…More frequent administration of analgesics for mild pain after laparoscopic surgery was reported in a retrospective study, suggesting that laparoscopic surgery is less painful [ 21 ]. However, retrospective reviews of medical records, with documentation of delivered analgesics, do not necessarily reflect patients' self-perception of pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery is reported to be associated with milder immunologic and inflammatory response [15] and have decreased morbidity and mortality, faster recovery and shorter hospital stay [16,17]. Decreased postoperative hospital stay duration always reflects faster postoperative recovery of intake of oral food, bowel function and physical activity [18][19][20][21][22][23]. As to CRC, similar resulted were found [24][25][26].…”
Section: Introductionmentioning
confidence: 72%